Microwave heating as a post-harvest treatment for white corn (Zea mays) against Sitotroga cerealella. Issue 3 (3rd July 2019) - García-Mosqueda, Cristina; Salas-Araiza, Manuel Darío; Cerón-García, Abel; Estrada-García, Héctor Javier; Rojas-Laguna, Roberto; Sosa-Morales, María Elena
Abstract: Microwave heating in white corn ( Zea mays L.) against Sitotroga cerealella was applied as a post-harvest treatment. Power levels of 293, 390 or 475 W were applied to batches of 250 g until reaching the target temperature of 50 °C in the grain centre and held for 3 min, followed by air-forced cooling during 3.5 min. One batch was left as a control without treatment. Thermocouples and thermal infrared camera were used to know the temperature and evaluate the heating uniformity. Heating times were 56, 40 and 37 s, for 293, 390 and 475 W, respectively, during which 100% of mortality in fourth instar larvae was achieved. The quality of treated white corn was followed throughout moisture content, water activity, bulk density, hardness, colour and germination ability. The proposed microwave treatments were effective for post-harvest corn disinfestation against S. cerealella, without affecting the quality of the grains, especially at 475 W.